RIFM fragrance ingredient safety assessment, 3, 7-dimethyl-1, 3, 6-octatriene, CAS registry number 13877-91-3. (March 2021) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment. 3, 7-Dimethyl-1, 3, 6-octatriene was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from 3, 7-dimethyl-1, 3, 6-octatriene and read-across analog myrcene (β-myrcene; CAS # 123-35-3) show that 3, 7-dimethyl-1, 3, 6-octatriene is not expected to be genotoxic and provide a calculated margin of exposure (MOE) >100 for the repeated dose toxicity and developmental and reproductive toxicity endpoints. The skin sensitization endpoint was completed using the dermal sensitization threshold (DST) for non-reactive materials (900 μg/cm 2 ); exposure is below the DST. The phototoxicity/photoallergenicity endpoints were evaluated based on ultraviolet (UV) spectra; 3, 7-dimethyl-1, 3, 6- octatriene is not expected to be phototoxic/photoallergenic. The local respiratory toxicity endpoint was evaluated using the threshold of toxicological concern (TTC) for a Cramer Class I material, and the exposure to 3, 7-dimethyl-1, 3, 6-octatriene is below the TTC (1.4 mg/day). The environmental endpoints were evaluated; 3, 7-dimethyl-1, 3, 6- octatriene was found not to be persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., Predicted Environmental oncentration/Predicted No Effect Concentration [PEC/PNEC]), are <1. Highlights: 3, 7-Dimethyl-1, 3, 6-octatriene; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.